2011
DOI: 10.1007/s00784-011-0553-8
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of 3D visualization for the removal of lower wisdom teeth: required sample size to prove non-inferiority of panoramic radiography compared to CBCT

Abstract: The availability of cone beam computed tomography (CBCT) and the numbers of CBCT scans rise constantly, increasing the radiation burden to the patient. A growing discussion is noticeable if a CBCT scan prior to the surgical removal of wisdom teeth may be indicated. We aimed to confirm non-inferiority with respect to damage of the inferior alveolar nerve in patients diagnosed by panoramic radiography compared to CBCT in a prospective randomized controlled multicentre trial. Sample size (number of required third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 70 publications
(60 reference statements)
1
12
0
2
Order By: Relevance
“…The author agrees with Roeder et al 13 and considers that CBCT scans should only be performed in high-risk wisdom tooth removals or for determination of the surgical approach and/or for coping with intraoperative complications. An effort to reduce the use of CBCT should be carried out when not necessary, in order to reduce radiation exposure and damage to the patient (Figure 4).…”
Section: Birpublicationsorg/dmfrsupporting
confidence: 77%
“…The author agrees with Roeder et al 13 and considers that CBCT scans should only be performed in high-risk wisdom tooth removals or for determination of the surgical approach and/or for coping with intraoperative complications. An effort to reduce the use of CBCT should be carried out when not necessary, in order to reduce radiation exposure and damage to the patient (Figure 4).…”
Section: Birpublicationsorg/dmfrsupporting
confidence: 77%
“…RCTs are often time consuming and, in addition, expensive to conduct, and therefore the number of patients included is often low, resulting in underpowered studies. 66 Epidemiological studies with lower evidence levels than that of RCTs have, moreover, evaluated the relationship between the use of CBCT for assessment of mandibular third molars and nerve injuries. A register study from Finland 67 concluded that the rapid increase in the availability of CBCT has caused no reduction in the number of permanent IAN injuries related to mandibular third molar removals as reported to the Finnish Patient Insurance Centre.…”
Section: Level 3-effect On Diagnostic Thinkingmentioning
confidence: 99%
“…A study from 2011 describes the almost impossible task to conduct an RCT measuring differences in permanent injuries owing to the need of very large samples. 33 Furthermore, the study highlighted that measuring differences in temporary disturbances also requires large samples. Therefore, the sample size has to be addressed and considered as a methodological limitation.…”
Section: Discussionmentioning
confidence: 99%